Determining the Corresponding Equations between Ejector Performance and Operating Conditions and Ejector Geometries by Using Response Surface Methodology - แสงมณี ชญานนท์ (Srinakharinwirot University Engineering Journal, 2018)
This study is to investigate the effect of variously important parameters on an ejector performance in steam ejector refrigeration system. The parameters are the operating conditions which are boiler and evaporator temperature and ejector geometries which are area ratio (AR) and area of throat ratio (ATR). Computational fluid dynamics (CFD) is employed to examine such effects with statistical research matrix design called Central Composite Design (CCD). The regression equation of relationships between parameter and ejector performance being entrainment ratio (Rm) and critical back pressure (CBP) are determined by using the response surface methodology (RSM). From simulation results, RSM analysis indicates that the operating conditions and ejector geometries have the significant effect on ejector performances. Furthermore, the quadratic model being properly with reliability above 95%. However, critical back pressure values given from the regression is slightly deviated because some parameters are not considered in this study.